Pembangunan Aplikasi Wakaf Indonesia Berbasis Blockchain - Suryaningsih, Sarah; Riandika, Yoga Afrizal; Hasanah, Arifa Nur; Anggraito, Sigit (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
Waqf has an important role in one aspect of Islamic in the economic sector. For document and evidence, waqf noted by nazir (receiver, guard, who maintains waqf) with paper and receipt. That is very vulnerable to losing waqf data which is because it is only documented by paper which is easy to lose or damaged. Based on that problem, then the waqf application based blockchain technology was developed which Aims to securing record data of waqf transaction so as not to be lost or hacked by irresponsible people, other than that for increase effectiveness in executing waqf transaction from wakif (a person who donates his property) side and nazhir (receiver, guard, who maintains waqf) side. The data collection methods used in this article are questionnaires and also interviews. This article confirms that waqf could be stored even better in security effort and saving data which is done digitally via website and android application. The results of the research which got a total result 95% with very feasible criteria, therefore the result of this research from this application have a very feasible score to be implemented for available waqf transaction because it has given more secure and effectiveness for the user.